2007
DOI: 10.1002/chin.200723225
|View full text |Cite
|
Sign up to set email alerts
|

Type II Polyketide Synthases: Gaining a Deeper Insight into Enzymatic Teamwork

Abstract: Type II Polyketide Synthases: Gaining a Deeper Insight into Enzymatic Teamwork -[277 refs.]. -(HERTWECK, C.; LUZHETSKYY, A.; REBETS, Y.; BECHTHOLD*, A.; Nat. Prod. Rep. 24 (2007) 1, 162-190; Inst. Pharm., Albert-Ludwigs-Univ., D-79104 Freiburg/Br., Germany; Eng.) -Lindner 23-225

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(110 citation statements)
references
References 1 publication
0
110
0
Order By: Relevance
“…SARP-like pathway-specific transcriptional activators are essential for angucycline production [4], however there is limited information on other regulatory genes within angucycline biosynthetic gene clusters. We recently showed that, besides transcriptional activator gene lanI , repressor gene lanK governs late steps of landomycins production in S. cyanogenus S136 [2].…”
Section: Discussionmentioning
confidence: 99%
“…SARP-like pathway-specific transcriptional activators are essential for angucycline production [4], however there is limited information on other regulatory genes within angucycline biosynthetic gene clusters. We recently showed that, besides transcriptional activator gene lanI , repressor gene lanK governs late steps of landomycins production in S. cyanogenus S136 [2].…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, the presence of a dedicated PKS initiation module leads to the formation of a non-acetyl derived diketide that is then elongated by the KS-CLF (Hertweck, et al, 2007; Moore and Hertweck, 2002). For example, the initiation module of the doxorubicin ( dps ) PKS (Grimm, et al, 1994) synthesizes a propionyl-CoA derived β-ketopentanoyl-ACP intermediate, whereas the R1128 ( zhu ) initiation module catalyzes formation of a butanoyl-, pentanoyl-, hexanoyl- or 4-methylpentanoyl-ACP thioester (Marti, et al, 2000) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Identification and characterization of the chd biosynthetic gene cluster (Hertweck et al, 2007). Using a KSa probe (PKSF-PKSR, Table S1; Methods), a genomic fragment containing the putative minimal PKS of the chd gene cluster was cloned, characterized and validated, and used to identify a larger overlapping clone from an A. sulphurea cosmid library which was subsequently sequenced (Methods).…”
Section: Resultsmentioning
confidence: 99%